CdS cubane type clusters encapsulated by rolling of single layer reduced graphene oxide sheets for enhanced mechanical energy harvesting - Kumar, Praveen; Ram, Farsa; Shanmuganathan, Kadhiravan; Luwang, Meitram Niraj (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Composites with Single Layer Graphene Oxide (SLGO) sheets are extremely difficult to achieve, irrespective of the current advancements in graphene composites research. The difficulties in exfoliating the graphite oxide (GO) was associated with a strong interaction among the edge sides of the adjacent layers. This in-turn barricades the foreign intruders to interact with the basal plane, thereby restraining one to form composites with SLGO sheets. In this work, we had successfully exfoliated GO through a spacer [Cd(OAc)(2) + polyethylene glycol (PEG)] to result in nano-engineered CdS cubane-type clusters in rolled up SLGO to form graphene oxide complex compound (GOCC), resembling carbon nanotubes (CNTs). The CdS cubane-type clusters were found to interacting with the carbon skeleton of rolled reduced SLGO sheet through a Manogate' structures, which was supported by density functional theory (DFT) calculations. Our theoretical study reveals that the obtained complex compound (GOCC) is thermodynamically more favourable than its ancestor materials (CdS cubane and empty CNT). Flexible piezoelectric nanogenerators (PENGs) fabricated from GOCC and thermoplastic polyurethane (TPU) resulted in output voltage (V-oc) of 4.5 V and output current of 0.4 mu A at applied force of 13 N. The nanoengineering helps to achieve superior mechanical energy harvesting performance for GOCC compared to pristine CdS, which demonstrate the potential of nanogate structures to enhance the intrinsic properties of materials.
Keywords: Graphene oxide complex compound; Nanogate structure; New material; Novel procedure; Piezoelectric nanogenerator; SLGO

Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT): a 3D sandwiched frameworks with efficient hydrogen production - Kumar, Praveen; Bajpai, Himanshu; Luwang, Meitram Niraj (Journal of Catalysis, 2023)
For over a decade, the structure, reactivity, and mechanism of graphene based photocatalysts have been of great interest for hydrogen (H2) generation. Several studies have been done on the edge side groups (ESGs) of graphene oxide (GO), but the basal plane groups (BPGs)-epoxide and hydroxide have acquired far less attention. This is because the GO layers are strongly held with van der waals forces as well as H-bonding which prevents the foreign body from entering inside the layers. To overcome these problems, this study presents the successful synthesis and application of four coordinated sandwiched (FCS) Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT) in rGO-CdS composite (A 3D sandwiched frame-work). Additionally, experimental outcomes have been further supported using density functional theory (DFT), which suggest that CdOTOT is more stable than its precursors as well as thermodynamically favourable. The CdOTOT shows high H2 production activity -67.5 mmol/g or 13.5 mmol/g/h in presence of 1 % Pt cocatalyst and sacrificial reagents (Na2S/Na2SO3). It is around 33 times higher than pristine CdS, and stable up to around 15 hrs without adding any cocatalyst. This mesmerising outcome is over with reported various CdS-rGO based photocatalysts. The higher activity was further explained through the proposed mechanism and observed low electronic work function of CdOTOT. This innovative and extend-able (with other metals) approach provides a revolutionary impact on numerous cutting-edge research applications like photocatalysis, water splitting, solar cell, etc.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: 2]; 3D sandwiched frameworks; Basal Plane Groups (BPGs); Cadmium (II) Organo Tetrakis-[1; hydrogen production; Oxathiin (CdOTOT)